LOCAL GOVERNMENT AUTONOMY AND GRASSROOTS DEVELOPMENT IN NIGERIA: FACT OR FARCE? - Onyemaechi Augustine, Eke (University of Nigeria Journal of Political Economy, 2022)
The derogation of powers of local governments by the higher tiers of government in Nigeria is increasingly raising concern over the country’s strides for development through grassroots. The epileptic performance of the local governments and challenges of extricating the system from the iron-clad grip of the state governments have questioned the autonomy of the Nigerian system. This paper takes an intellectual excursion into the dynamics of Nigerian local government system to unearth inter alia, the rationale behind: the development of local government system; Nigeria’s local government autonomy; and problems and prospects of the system, over the years. It, therefore, argues that states’ abrasive interferences on the autonomy of local government system constitutes an affront against good governance and democratic federalism. The satrapic conflict in the federal-state-local government relations over the control and supervision of the local governments by the federal and state levels constrain local governments’ autonomy and their power of initiating policies and programmes by the local authorities for grassroots development in Nigeria.